Vaccine-like and Prophylactic Treatments of EAE with Novel I-Domain Antigen Conjugates (IDAC): Targeting Multiple Antigenic Peptides to APC - Büyüktimkin, Barlas (2012)
The objective of this work is to utilize novel I-domain antigenic-peptide conjugates (IDAC) for targeting antigenic peptides to antigen-presenting cells (APC) to simulate tolerance in experimental autoimmune encephalomyelitis (EAE). IDAC-1 and IDAC-3 molecules are conjugates between the I-domain protein and PLP-Cys and Ac-PLP-Cys-NH(2) peptides, respectively, tethered to N-terminus and Lys residues on the I-domain. The hypothesis is that the I-domain protein binds to ICAM-1 and PLP peptide binds to MHC-II on the surface of APC; this binding event inhibits the formation of the immunological synapse at the APC-T-cell interface to alter T-cell differentiation from inflammatory to regulatory phenotypes. Conjugation of peptides to the I-domain did not change the secondary structure of IDAC molecules as determined by circular dichroism spectroscopy. The efficacies of IDAC-1 and -3 were evaluated in EAE mice by administering i.v or s.c. injections of IDAC in a prophylactic or a vaccine-like dosing schedule. IDAC-3 was better than IDAC-1 in suppressing and delaying the onset of EAE when delivered in prophylactic and vaccine-like manners. IDAC-3 also suppressed subsequent relapse of the disease. The production of IL-17 was lowered in the IDAC-33 treated mice compared to those treated with PBS. In contrast, the production of IL-10 was increased, suggesting that there is a shift from inflammatory to regulatory T-cell populations in IDAC-33treated mice. In conclusion, the I-domain can effectively deliver antigenic peptides in a vaccine-like or prophylactic manner for inducing immunotolerance in the EAE mouse model.